Structural, elastic, and optical properties of holmium–ytterbium-doped borotellurite glass for possible applications in optical fiber sensing - Mazlan, M.; Winie, Tan; Sazali, E. S.; Malek, M. F.; Zaid, M. H. M.; Azlan, M. N.; Hisam, R. (Springer Science and Business Media Deutschland GmbH, 2024)
A series of mixed glass formers (MGF) with varying compositions denoted as (79-x)B2O3-xTeO2-20Li2O-0.5Ho2O3-0.5Yb2O3 (x = 0–50 mol%) were prepared using the melt-quenching technique. This aim of this study was to examine the effect of combining glass formers TeO2 and B2O3 on the structural, DC conductivity, elastic, and optical properties of the glass system. XRD measurements confirmed the amorphous nature of the glass samples. Structural analysis revealed a rivalry between the TeO2 and B2O3 formers. It was observed that the bridging oxygen (BO) indicated by the BO4 functional group decreases gradually at x ≥ 40 mol%, implying that non-bridging oxygen (NBO) units, denoted by BO3, become dominant beyond 40 mol%. The variation in DC conductivity showed a non-linear behaviour upon addition of TeO2, with the conductivity increasing to a maximum value at x = 30 mol% before decreasing at x > 30 mol%. Interestingly, the conductivity showed a slight decline at x = 40 mol%, possibly resisting a decrease due to the mixed glass former effect (MGFE). Elastic moduli such as CL, Ke and Y exhibited a non-linear decrease between 10 ≤ x ≤ 30 mol% and reached a lowest value for x = 40 mol%, which coincided with the maximum of DC conductivity attributed to MGFE. Quantitative analysis of ultrasonic data, utilizing bulk compression and ring deformation models, revealed that the Kbc/Ke value is maximum at x = 40 mol%, implying a reduction in ring deformation within the MGFE region. UV–Vis spectroscopy demonstrated that with increasing TeO2 content, Eopt and Eopt’ decreased except for x = 40 mol%. The refractive index, n also increased except at x = 40 mol%. The alternating dominance of BO and NBO in the MGFE region led to this conclusion.